S61 Risk factors and short-term outcomes of developing postoperative pulmonary complications after vats lobectomy. (15th November 2016) - Agostini, P; Lugg, ST; Adams, K; Smith, T; Kalkat, M; Rajesh, PB; Steyn, RS; Naidu, B; Rushton, A; Bishay, E
Abstract : Introduction: Postoperative pulmonary complications (PPC), such as pneumonia and atelectasis are associated with poor outcomes following thoracotomy and lung resection, with risk factors identified. 1, 2 Video-assisted thoracoscopic surgery (VATS) is increasingly performed, however, there are varying reports regarding the incidence of PPC with little is known about their effect on short-term outcomes or potential risk factors. Methods: A prospective observational study of consecutive patients undergoing VATS lobectomy was performed in a regional centre (2012–2016). Exclusion criteria included re-do VATS/completion lobectomy. All patients received physiotherapy assessment/intervention as necessary from postoperative day 1 (POD1). The presence of PPC was determined daily using the Melbourne Group Scale. Outcomes included hospital length of stay (LOS), intensive therapy unit (ITU) admission and hospital mortality. Results: 287 patients underwent VATS lobectomy, 2 patients undergoing completion lobectomy were excluded. Of 285 patients; 137 were male (48%), median (IQR) age of 69 years (13) and mean (±SD) FEV1 of 87% (±19). PPC developed in 21 patients (7.4%); the median day that PPC developed was postoperative day 3 (Figure 1 ). Patients who developed a PPC had a significantly longer hospital LOS (4 vs 3 days), higher rate of ITU admission (25% vs 0%) and higher hospital mortality (14% vs 0%) (p < 0.001). Current smoking and COPD diagnosis were significantly different on univariate analysis (p < 0.05), but on forward stepwise logistic regression, only current smoking was a significant independent risk factor for PPC (p = 0.015). Those with PPC required significantly more physiotherapy contacts/time, with more specific pulmonary therapy and emergency out-of-hours therapy. Conclusions: Patients undergoing VATS remain at risk of developing a PPC associated with significantly worse short-term morbidity and mortality. Patients that develop a PPC following VATS required increased postoperative physiotherapy compared to non-PPC patients. Current smoking is an independent risk factor for PPC development following VATS, thus vigorous addressing of preoperative smoking cessation is urgently needed. References: Agostini P, et al . Postoperative pulmonary complications following thoracic surgery: are there any modifiable risk factors? Thorax 2010;65 (9):815–8. Lugg ST, et al . Long-term impact of developing a postoperative pulmonary complication after lung surgery. Thorax 2016;71 (2):171–6.